2004
DOI: 10.1038/sj.bmt.1704711
|View full text |Cite
|
Sign up to set email alerts
|

rhG-CSF does not affect the phenotype of adult donor peripheral blood NK cells

Abstract: Summary:Considerable evidence in preclinical models as well as in human transplantation now suggests that donor-derived natural killer (NK) cells can contribute to alloimmune recognition of recipient residual tumour cells. This makes the NK cell population an attractive target for in vitro or in vivo manipulations, in order to improve the antitumour effect of allogeneic transplantation. However, conditions in which allogeneic donor cells are collected vary; several reports have emphasised the different phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(47 reference statements)
0
4
1
Order By: Relevance
“…In contrast with previously reported data showing no significant effect of G-CSF on NK subpopulations [23,39], our results show that although in PB the NK cell fractions were significantly down-regulated by G-CSF, in BM a modest increase of both CD3 − CD16 + and CD3 − CD56 + was detected. This activity of G-CSF on BM NK cells might be of particular importance in G-BM haploidentical transplant because NK cells are important effector cells in mediating the graft-versusleukemia effect.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with previously reported data showing no significant effect of G-CSF on NK subpopulations [23,39], our results show that although in PB the NK cell fractions were significantly down-regulated by G-CSF, in BM a modest increase of both CD3 − CD16 + and CD3 − CD56 + was detected. This activity of G-CSF on BM NK cells might be of particular importance in G-BM haploidentical transplant because NK cells are important effector cells in mediating the graft-versusleukemia effect.…”
Section: Discussioncontrasting
confidence: 99%
“…One study [34] showed no effect of rhG-CSF administration on the PB NK cell phenotype (defined as CD3 - /CD56/CD16 + or CD3 - /CD56 + cells) of adult PBPC donors.…”
Section: Immunologic Effects Of Rhg-csfmentioning
confidence: 99%
“…G‐CSF administration typically leads to a two‐ to threefold increase in the number of eosinophils and enhanced eosinophil adhesion 11,12 . Existing data indicate minimal or no impact of G‐CSF on natural killer cells 13 . The neutrophil kinetics after G‐CSF administration have been well characterized for many years.…”
Section: G‐csfmentioning
confidence: 99%
“…11,12 Existing data indicate minimal or no impact of G-CSF on natural killer cells. 13 The neutrophil kinetics after G-CSF administration have been well characterized for many years. G-CSF administration increases polymorphonuclear (PMN) leukocyte production, expands the promyelocye-myelocyte compartment of the marrow (however, the percentage of marrow blasts remains unchanged), and reduces PMN leukocyte tissue migration.…”
Section: G-csfmentioning
confidence: 99%